(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article purposes to discuss about the importance of bilingualism, beneficial sides of bilingualism in early childhood and children’s future life. Furthermore there is a research presented as a questionnaire. The research study was conducted among 70 kindergarten teachers of Uzbekistan. Research question: which benefits of bilingualism are admitted by kindergarten teachers ?